Implikasi Pemilihan Kepala Daerah secara Langsung terhadap Kebijakan Ketahanan Pangan dan Suboptimal Lahan Pertanian di Provinsi Sumatera Selatan - Andries Lionardo (Seminar Nasional Lahan Suboptimal, 2019)
Lionardo A. 2019. Implications of direct regional head election on food security and suboptimal agricultural land policies in South Sumatra Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019. Palembang  4-5 September 2019. pp. 535-545.  Palembang: Unsri Press. The mechanism of direct selection of regional heads should have implications for the condition of food security which is more beneficial to the lives of people in South Sumatra. This is because for the people of Indonesia rice is a staple food that is difficult to replace. Thus the policy accountability will be the responsibility of the government to fulfill it every year. The direct election of regional heads should not result in a populist policy in agriculture. The new autonomy must have an impact on the problem of social, economic and community income that can meet basic food needs for people in South Sumatra. Food Security Policy that has long been rolled out has an impact on poverty in rural areas that are difficult to overcome, the government inevitably if it wants to improve the economy of farmers in rural areas must make a policy related to three components, namely improving the welfare of farmers, equilibrium of market mechanisms, and fairness of management of agricultural land. The implementation of Regional Regulation Number 21/2004 on the protection of sustainable food agriculture land must be on the agenda setting of the regional head's policy as the result of direct regional head election in developing the Food Security program for rural progress. Thus, the function of suboptimal agricultural land is agriculture to industrial areas. The purpose of this study is to look at the extent of the Implications of Direct Regional Head Election for Food Security and Suboptimal Agricultural Land Policies in South Sumatra Province.Keywords: direct election, food security, public policy